THE PROFILE OF TEACHERS’ TECHNIQUES, MEDIA AND MATERIAL OF TEACHING ENGLISH VOCABULARY TO YOUNG LEARNERS APPLIED AT AURA SUKMA INSANI KINDERGARTEN (A CASE STUDY) - P. W. E., Mahadewi; -, Sudirman; N. K., Wedhanti (Jurnal Pendidikan Bahasa Inggris undiksha, 2018)
AbstractThis research aimed to describe (1) the teachers’ techniques, media and material in teaching English vocabulary to young learners at Aura Sukma Insani Kindergarten and (2) the problems faced by the teachers in applying the techniques, media and material in teaching vocabulary. This research was a case study under the form of qualitative design. The subjects of the study were the English teachers in Aura Sukma Insani Kindergarten. The instruments used in collecting the data were the researcher herself, interview guide, video recorder, observation checklist and field note. The data analysis was conducted through four stages namely data collection, data reduction, data display and conclusion drawing. The result of analysis showed that the teachers applied various teaching strategies with the support of various teaching media to teach vocabulary. The variation enabled the students to have much exposure to the vocabularies. Moreover, the problems faced by the teachers in teaching vocabulary were about the students’ behavioral management, attention management and dependence toward their teachers.Key words: technique, media, material, vocabulary, young learners